Advanced Engineering Mathematics / Third Edition - O'Neil Peter V (Wadsworth Publishing Company, 1991)
Introduction to Ordinary Differential Equations, First Order Differential Equations, Linear Section Order Differential Equations, The Laplace Transform, Additional Topics in Ordinary Differential Equations, Nonlinear Differential Equations and Stability, Calculus of Variations, Difference Equations, Linear Algebra and Systems of Differential Equations, Vector and Vector Spaces, Matrix Slutions of Systems of Differential Equations, Vector Calculus, Vector Differential Calculus, Vector Integral Calculus, Fourier Analysis and Boundary Value Problems, Complex Analysis, Integration in the Complex Plane, Singularities and the Residue Theorem, Conformal Mappings, Index.